2017
DOI: 10.1515/amm-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Microstructure and Mechanical Properties of Hot Rolled 23MnB4 Steel Grade for Cold Upsetting

Abstract: The article presents the results of tests of influence of the thermo-mechanical treatment parameters on the mechanical properties and microstructure of steel 23MnB4 for cold-upsetting. Measurements of the ferrite grains and pearlite colonies were conducted with the use of Met-Ilo program supplemented by additional procedures dedicated to structure analysis of ferritic-pearlitic steel. The process of rolling was conducted in simulation in semi-continuous finishing train arrangement with different temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…However, no technological studies of the obtained wire rod were carried out in these works. The research results presented in this work are consistent with the results published in [33][34][35]. Nonetheless, as the research published in [3] showed, after the deformation of 20MnB4 steel for cold upsetting, at a rolling end temperature of about 750 • C, microstructure banding is obtained, which reduces the technological properties of the wire rod, regardless of the cooling rate used on the roller conveyor.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, no technological studies of the obtained wire rod were carried out in these works. The research results presented in this work are consistent with the results published in [33][34][35]. Nonetheless, as the research published in [3] showed, after the deformation of 20MnB4 steel for cold upsetting, at a rolling end temperature of about 750 • C, microstructure banding is obtained, which reduces the technological properties of the wire rod, regardless of the cooling rate used on the roller conveyor.…”
Section: Introductionsupporting
confidence: 91%
“…The authors of papers [33][34][35] were also involved in improving the quality of steel wire rod for cold upsetting. They stated that in the case of the studied steel, the best complex of mechanical properties of the finished product can be obtained after rolling in the final passes at 750 • C and subsequent cooling of the wire rod at a rate of 5 • C/s.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the surface coverage of the abrasive material particles was determined with quantitative metallography methods using Metillo software [ 22 , 23 , 24 , 25 , 26 , 27 ]. The process was as follows: Microscope image loaded into Metillo programme ( Figure 8 A).…”
Section: Methodsmentioning
confidence: 99%
“…In the technical literature on the rolling process, it is possible to find studies dealing with the influence of the production process parameters on the quality (mainly microstructure and mechanical properties) of the finished product [14][15][16][17][18][19][20][21][22][23][24][25]. Several groups of steels for wire rod production were described in [14], such as interstitial free (IF) ferritic steels, ferritic/martensitic steels, and pearlitic micro-alloyed steels.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this study have shown that an important factor in terms of the range of applications of the obtained wire rod is the significant increase in its capacity for further direct cold plastic working processes. Studies [15][16][17][18][19]21] deal with the rolling processes of wire rods made from high-carbon steels. In these studies, the effects of temperature and cooling conditions on the microstructure and properties of the wire rod were analyzed.…”
Section: Introductionmentioning
confidence: 99%